Pandangan Tokoh MUI Serdang Bedagai terhadap Pemilihan Pasangan dalam Pernikahan karena Undian: Studi Kasus Desa Pematang Setrak Kecamatan Teluk Mengkudu - Fakhri, Muhammad Puji; Siregar, Ramadhan Syahmedi (AL-SULTHANIYAH, 2025)
This study aims to explore the perspective of the Indonesian Ulema Council (MUI) of Serdang Bedagai Regency on the practice of marriage through a lottery system, which took place in Pematang Setrak Village, Teluk Mengkudu Subdistrict, as a response to an out-of-wedlock pregnancy case. The practice involved drawing lots among several men allegedly involved to determine who would marry the pregnant woman, in order to preserve family honor and clarify the child’s lineage. This research employed a qualitative field method through interviews with local MUI figures. The findings indicate that the MUI views such a marriage as valid under Islamic law, as long as it fulfills the essential requirements and pillars of marriage, although the lottery method is not normative in Islamic jurisprudence. The MUI also emphasizes the need for religious counseling and post-marital guidance to ensure the couple can build a family based on Islamic values. This study contributes to the contemporary discourse on Islamic law by addressing how it interacts with emerging social practices.